Facial, vocal and musical emotion recognition is altered in paranoid schizophrenic patients. Issue 1 (30th September 2015) - Weisgerber, Anne; Vermeulen, Nicolas; Peretz, Isabelle; Samson, Séverine; Philippot, Pierre; Maurage, Pierre; De Graeuwe D'Aoust, Catherine; De Jaegere, Aline; Delatte, Benoît; Gillain, Benoît; De Longueville, Xavier; Constant, Eric
Abstract: Disturbed processing of emotional faces and voices is typically observed in schizophrenia. This deficit leads to impaired social cognition and interactions. In this study, we investigated whether impaired processing of emotions also affects musical stimuli, which are widely present in daily life and known for their emotional impact. Thirty schizophrenic patients and 30 matched healthy controls evaluated the emotional content of musical, vocal and facial stimuli. Schizophrenic patients are less accurate than healthy controls in recognizing emotion in music, voices and faces. Our results confirm impaired recognition of emotion in voice and face stimuli in schizophrenic patients and extend this observation to the recognition of emotion in musical stimuli. Highlights: We tested emotion recognition capacities in schizophrenic patients (SP). SP show deficits in recognition of musical, vocal and facial emotional stimuli. SP present deficits in the visuals as well as general auditory domain. SP often use music as a coping strategy. New research on the use of music for the treatment of SP is suggested.